All-silicon metasurfaces for polarization multiplexed generation of terahertz photonic orbital angular momentum superposition states. Issue 16 (9th April 2021) - Li, Jie; Wang, Guocui; Zheng, Chenglong; Li, Jitao; Yang, Yue; Zhang, Zhang; Yang, Maosheng; Zhao, Hongliang; Li, Fuyu; Tang, Tingting; Wu, Liang; Li, Jining; et al.
Abstract : The superposition state of photonic orbital angular momentum (OAM) has more degrees of freedom than pure photonic orbital angular momentum, with rich physical implications and engineering application possibilities. Abstract : The superposition state of photonic orbital angular momentum (OAM) has more degrees of freedom than pure photonic orbital angular momentum, with rich physical implications and engineering application possibilities. Here we propose a scheme for polarization multiplexed terahertz OAM superposition state generation using an all-silicon metasurface. Two types of spatially interlaced metasurface OAM superposition state generators are designed and experimentally verified, which realize the generation of polarization-dependent single or multiple terahertz vortex interference beams. The first type of metasurface consists of polarization-maintaining silicon pillar arrays, which can switch the transmitted terahertz beam between different OAM superposition states. The analyzer direction of the superposition state is always consistent with the incident polarization. The second type of metasurface introduces units with a polarization conversion function, so that the analyzer direction of the OAM superposition state under different incident polarizations is always kept unchanged. In addition, the proposed metasurfaces can also generate a longitudinal electric field component and manipulate the superposition state of OAM. Both types of metasurfaces show excellent performance of efficient generation and switching of terahertz OAM superposition states. This method provides a new idea for photonic OAM manipulation based on metasurfaces.